2021
DOI: 10.1088/1741-2552/abf68a
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised machine learning can delineate central sulcus by using the spatiotemporal characteristic of somatosensory evoked potentials

Abstract: Objective. Somatosensory evoked potentials (SSEPs) recorded with electrocorticography (ECoG) for central sulcus (CS) identification is a widely accepted procedure in routine intraoperative neurophysiological monitoring. Clinical practices test the short-latency SSEPs for the phase reversal over strip electrodes. However, assessments based on waveform morphology are susceptible to variations in interpretations due to the hand area’s localized nature and usually require multiple electrode placements or electrode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 57 publications
4
9
0
Order By: Relevance
“…Channels 209, 210, 212, and 215, expected to be located posterior to the central sulcus, exhibit the desired SSEP waveform with a negative peak (N) followed by a positive (P). This pattern aligns with the typical cortical response seen in somatosensory processing 3 , 30 . These findings indicate the successful activation of sensory pathways and the propagation of neural signals across the primary somatosensory cortex.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Channels 209, 210, 212, and 215, expected to be located posterior to the central sulcus, exhibit the desired SSEP waveform with a negative peak (N) followed by a positive (P). This pattern aligns with the typical cortical response seen in somatosensory processing 3 , 30 . These findings indicate the successful activation of sensory pathways and the propagation of neural signals across the primary somatosensory cortex.…”
Section: Discussionsupporting
confidence: 85%
“…These inter-subject differences in peak latencies appear in comparable studies and may reflect variations in neural conduction velocities or discrepancies in the processing mechanisms of the somatosensory systems. However, the timing of the 2nd N peak has generally higher latencies, as found in comparative literature 3 , 26 , 30 . This could be explained by the lower bandpass cutoff at 20 Hz, which is lower compared to other studies but has shown the best results for delineation with the uHD EEG.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…MacDonald et al 2019, Asman et al 2021). PRT consists of visually detecting specific features of the somatosensory evoked potentials (SSEPs) evoked by median nerve stimulation (MNS) and recording from electrocorticographic (ECoG) electrode grids placed on the surface of the cortex.…”
Section: Introductionmentioning
confidence: 99%